The Influence of Building Quality, Strategic Location, and Price on the Decision to Purchase Subsidized Housing in the Cileungsi Area - Yosua B Rachmat; Harlyn Siagian; Judith Tagal Gallena Sinaga (Dinasti International Journal of Education Management And Social Science, 2024)
This study aims to present a comprehensive depiction of the factors influencing the decision-making process regarding the purchase of subsidized housing, focusing specifically on variables such as building quality, strategic location, and price. The research objectives include identifying the key variables impacting the choice of acquiring subsidized housing in the Cileungsi region through a quantitative descriptive approach. Utilizing purposive sampling, the study surveyed one hundred local residents who recently acquired homes through government assistance programs. Structural Equation Modeling (SEM) employing variance-based methods or component-based structural equation modeling, specifically Partial Least Squares (PLS), was utilized for data analysis. The anticipated outcomes of this investigation are expected to contribute significantly to understanding consumer behavior in the context of subsidized housing purchases in Cileungsi. Moreover, the application of PLS analysis methods is poised to provide an in-depth comprehension of the interrelationships among variables within the tested model and furnish strategic recommendations for developers of subsidized housing and pertinent stakeholders to enhance product appeal.